Chemical attributes at Oxisol spatialy related to common been productivity and yield features in Selvíria (MS) - Montanari, Rafael; Rodrigues, Gleice Gomes; Carvalho, Morel de Passos e; Dalchiavon, Flávio Carlos; Machado, Flávia Cristina; Gonzalez, Antonio Paz (Revista de Ciências Agroveterinárias, 2013)
The common bean (Phaseolus vulgaris L.) stands out in the eating habits of Latin Americans for having great importance in providing the nutritional diet of protein, iron and carbohydrates, with Brazil being the largest producer of the vegetable. In the season 2006/2007, in Selvíria, MS , located in the Brazilian Cerrado, we evaluated the spatial variability of bean, depending on the chemical properties of Oxisol using a minimum tillage system, irrigated with center pivot. The objective of this work was to select the soil attributes that have the best spatial and linear correlation, to explain the variability of common bean grain yield. A geostatistical grid, with 117 sampling points, was installed to collect the soil and plant data in an area of 2,025 m2 with homogeneous slope of 0.055 m m-1. The common bean grain yield (GY), number of haricot per plant (NHP), number of grains per haricot (NGH), number of grains per plant (NGP) and weight of one hundred grains (DHG), represented the attributes of the plants, while P, OM, pH, were the soil chemical attributes collected at three depths (0.00-0.10 m, 0.10-0,20 m e 0.20-0.30 m). The average common bean grain yield was a consequence of lower plant population provided by that the system, this may have been caused by a decrease in organic matter content.